Oil Market, Nuclear Energy Consumption and Economic Growth: Evidence from Emerging Economies - Naser, Hanan (International Journal of Energy Economics and Policy, 2014)
This paper empirically examines the relationship between oil consumption, nuclear energy consumption, oil price and economic growth in four emerging economies (Russia, China, South Korea, and India) over the period from 1965 to 2010. Applying a modified version of the granger causality test developed by Toda and Yamamoto, we find that the level of world crude oil prices (WTI) plays a crucial role in determining the economic growth in the investigated countries. The results suggest that there is a unidirectional causality running from real GDP to oil consumption in China and South Korea, while bidirectional relationship between oil consumption and real GDP growth appears in India. Furthermore, the results propose that while nuclear energy stimulates economic growth in both South Korea and India, the rapid increase in China economic growth requires additional usage of nuclear energy. Keywords: nuclear energy consumption; oil consumption; economic growth; oil prices; Granger causality test JEL Classifications: Q40; Q43; Q48